SAE Technical Paper Series 1988
DOI: 10.4271/881316
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Impingement in a Direct Injection Diesel Engine

Abstract: Os10hm an O memo sii necmsawy and identify by block nhmber) I LASISTAcr ('bmo am vowwm w mnomy anidglml~ by Nlock minbmr) AIsTUACT 014 REPRINT 00 wims or I~ 010 41 o,0L 59COU tr Ii 9jrThsP2fIww *1T lyme 6aiVnbe of the code at the bottom Of thefirst Page of this paper Indicates SAES consent that copies of the paper may be made fot personal or intewnl use, or for the peusonal or Internal us of specific clients. This consent Is given on the condition. however. that the Copier Pay the stated per article copy fee t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Figure 8 compares calculated impinged spray penetration (indicated by lines) with the experimental data (indicated by symbols) generated by high-speed pho tography in the constant-volume bomb under simulated diesel engine conditions (air density) (28) for three differ ent fuel rail pressures (4.7, 6.1 and 7.8 MPa). The predic tions compare well except for some overprediction after 0.6 ms, which may be due to the fact that experimental data were obtained from high-speed movies of the backlit spray pattern and the start of injection could not be determined exactly because of the limited frame rate of the camera (28). Figure 9 compares the computed volume of the impinging spray at three ambient densities of 6.15, 9.23 and 12.3 kg/m 3 (indicated by lines) with the experimen tal data of Katsura et al (35) (indicated by symbols).…”
Section: Wall Jet Predictionsmentioning
confidence: 80%
See 3 more Smart Citations
“…Figure 8 compares calculated impinged spray penetration (indicated by lines) with the experimental data (indicated by symbols) generated by high-speed pho tography in the constant-volume bomb under simulated diesel engine conditions (air density) (28) for three differ ent fuel rail pressures (4.7, 6.1 and 7.8 MPa). The predic tions compare well except for some overprediction after 0.6 ms, which may be due to the fact that experimental data were obtained from high-speed movies of the backlit spray pattern and the start of injection could not be determined exactly because of the limited frame rate of the camera (28). Figure 9 compares the computed volume of the impinging spray at three ambient densities of 6.15, 9.23 and 12.3 kg/m 3 (indicated by lines) with the experimen tal data of Katsura et al (35) (indicated by symbols).…”
Section: Wall Jet Predictionsmentioning
confidence: 80%
“…-mJO -pJ Pl ) + (m v /m,Xl -pjp } ) (23) In the absence of evaporation (m v = 0), equation (23) reduces to the form of reference (7), that is The equations (28) to (31) contain the derivatives of four dependent variables, viz. concentration, velocity, wall jet thickness and jet direction; of these four derivatives, the value of the directional derivative is available directly from equation (31).…”
Section: Prediction Of Spray Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of this model was also tested by Naber (1988b) under simulated diesel pressures and densities at ambient temperature in a bomb study. The study found that the spray rebound was under-estimated by the model.…”
Section: Model Developmentmentioning
confidence: 99%